"Growing Apart": The Rise of Inequality. (March 2014) - Ward, Kate; Himes, Kenneth R.
Economic inequality, particularly in the areas of income and wealth, has been steadily expanding in the United States. This reality is an issue for other nations as well. This article examines reasons why economic inequality deserves more attention from moral theologians. It also reviews recent literature on the topic and the need to restore equality of opportunity as a genuine aspect of American life.